Urban gardens in Antiquity: The case of Gerasa/Jerash in Jordan. (December 2022) - Holdridge, Genevieve; Simpson, Ian; Lichtenberger, Achim; Raja, Rubina; Kinnaird, Tim C.; Sanderson, David; Kristiansen, Søren M.
Graphical abstract: Highlights: RMS; Pleistocene origin and human impact; urban gardening and irrigation. We studied human use of Red Mediterranean Soils at a Classical urban site located in Jordan. Pleistocene origin and later human impact clearly reflected by micromorphological characteristics. Combined evidence suggests within city gardening and irrigation during especially Roman occupation. Abstract: In the Eastern Mediterranean, where some of the earliest known urban cities are located, relatively little is known about urban soils in archaeological contexts. Red Mediterranean Soil (RMS) is a hallmark of the Mediterranean region while the impact of long-term urbanization on RMS material is understudied. In this article we present evidence of RMS from the longue durée cityscape of Jerash, Jordan, to determine how humans have used, modified and impacted RMS material in an urban context. Thin-sections were made of twelve RMS samples, and micromorphological studies on several in-situ but disturbed soils adjacent to bedrock were conducted, spanning the initial surface soil disturbances in the Hellenistic and Roman period occupation, as well as transported RMS material spanning the Roman through Umayyad periods (until the earthquake of 749 CE). We compared the on-site inner-urban red soils to natural RMS in the area and found that some characteristics reflect their origin in the Pleistocene soils, while other traits reflect human impact related to urban activities. The majority of the on-site samples contained evidence comparable to modern centers, including changes of structure, texture, inclusions, as well as high levels of contamination of heavy metals and phosphorus (P), which combined are strong signs of urban activity. Evidence including textural pedofeatures, fragmented peds, mixed fabrics, sorting of silt-sized material likely reflect the use of RMS in urban gardens and cultivation. Black carbon inclusions within the fabric contain evidence for burning of organic matter in connection with various anthropogenic activities, likely re-dispersed via aeolian and water erosion processes. Heavy metal enrichments, which are associated with production and artisanal activities, may also have been disseminated by both aeolian and surface water processes, possibly in conjunction with irrigation undertaken with polluted water. Contrasting soil fabrics and inclusion features observed in thin section together with elemental analayses characterizes the nature of urban cultivation in its environmental context at Jerash, where city life was maintained for over 800 years. With cultivated soils in urban areas increasingly evidenced in archaeological stratigraphies from different regions of the world, our approach offers new insight into the vital contributions that these soils and their management has made to the food security, resilience and longevity of early city life.